Rapid response to mass shootings - Reeping, Paul M. (Criminology & public policy, 2020)
Research We conducted a scoping review of literature indexed in the National Library of Medicine's journal citation database, MEDLINE, and Scopus to identify articles in which the rapid response of hospital staff, emergency medical services personnel, the police, and the public to mass shootings is covered. Sixty-five articles were included, and critical themes related to reducing the harm from a mass shooting were summarized. Policy Implications According to our findings, when mass shootings occur in the United States, several evidence-informed steps can be taken from the moment the first bullet is fired until the last injured individual is transported to the hospital to promote a rapid response that can reduce death and disability. Ten recommendations are made ranging from recognition of the need for rapid response and bystander training to triage and transport training of police and avoidance of over-response.